2013
DOI: 10.1111/adj.12050
|View full text |Cite
|
Sign up to set email alerts
|

Minimum intervention dentistry and the management of tooth wear in general practice

Abstract: The incidence of tooth wear, or non-carious tooth surface loss (NCTSL), is increasing and oral rehabilitation of patients with non-carious tooth loss requires strategies that address all the factors relevant to the aetiology and pathogenesis of the condition. The multifactorial nature of tooth wear and the variability in its clinical presentation provides treatment challenges for the clinician and successful management must be more than just restoration. Management must include an appropriate mix of preventive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 41 publications
(57 reference statements)
1
18
0
3
Order By: Relevance
“…Thus, dental erosion has been recognized as an occupational hazard in professional wine tasters, emphasizing the need for early detection and management in accordance with the minimal intervention philosophy . Consequently, a key priority area in dental erosion research is the assessment of the fundamental mechanisms involved in early stages of erosion that may lead to the development of more effective preventive strategies …”
Section: Introductionmentioning
confidence: 99%
“…Thus, dental erosion has been recognized as an occupational hazard in professional wine tasters, emphasizing the need for early detection and management in accordance with the minimal intervention philosophy . Consequently, a key priority area in dental erosion research is the assessment of the fundamental mechanisms involved in early stages of erosion that may lead to the development of more effective preventive strategies …”
Section: Introductionmentioning
confidence: 99%
“…3 In order to prevent a lifetime of compromised dental health that may require complex and extensive rehabilitation, it is now generally recommended that, in accordance with the principles of minimal intervention dentistry, emphasis should be placed on early diagnosis and prevention before restorative management is considered. [4][5][6][7] Reported recent increases in the prevalence of erosion in children and young adults have been attributed to extrinsic erosion from increased consumption of acidic beverages, 8 with the relative effect of erosion due to intrinsic factors generally being considered minor.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results showed that the variability observed in 2002 toward caries management decisions was persisting in 2012. © 2015 S. Karger AG, Basel In modern cariology, minimum intervention (MI), based on prevention and on intervention limited to the absolute minimum, is considered to be the most logical choice -both from a medical and an ethical standpoint [Bowley, 2002;Darby and Ngo, 2013;Elderton, 2003;Farah et al, 2013;Featherstone and Doméjean, 2012;Meyers, 2013;Pitts and Ekstrand, 2013;Sheiham, 2002].…”
mentioning
confidence: 99%